Transcatheter aortic valve replacement in low-risk patients: an updated meta-analysis of randomized controlled trials - Roel Meeus; Pavell Dhondt; Jesslyn Hariyanto; Hadiah Ashraf; Caterina Lecchi; Caroline O. Fischer-Bacca; Leen Van Langenhoven; Lennert Minten; Christophe Dubois (International Journal of Cardiology: Heart & Vasculature)
Background: Transcatheter aortic valve replacement (TAVR) is increasingly used in patients with aortic valve stenosis (AS) at low risk for surgical aortic valve replacement (SAVR), despite uncertainty regarding medium and long-term clinical outcomes. Objectives: We performed an updated meta-analysis comparing TAVR with SAVR in this population. Methods: We searched PubMed, EMBASE and Cochrane Central for randomized controlled trials (RCT) comparing TAVR with SAVR in low-risk patients with either bicuspid or tricuspid AS. Outcomes of interest were all-cause mortality, rehospitalization and stroke at 30 days, 1 year and up to 5 years follow-up. Results: We included six RCTs with in total 4487 patients, mean age 74.2 ± 5.5y and of which 50.1 % underwent TAVR. The STS-PROM Score was similar for TAVR and SAVR (2.1 ± 0.7 vs. 2.2 ± 0.8 %). Thirty-day all-cause mortality showed a borderline significant difference favoring TAVR (RR 0.55; 95 % CI 0.30–1.01; p = 0.05). One-year all-cause mortality was significantly lower for TAVR (RR 0.60; 95 % CI 0.41–0.98; p = 0.01), while no differences were seen at 5-year follow up (RR 1.02; 95 % CI 0.81–1.29; p = 0.85). TAVR was associated with reduced 30-day (RR 0.67; 95 % CI 0.46–0.95; p = 0.03) and one-year rehospitalization rates (RR 0.72; 95 % CI 0.53–0.98; p = 0.04). Stroke rates at 30 days (RR 0.78; 95 % CI 0.48–1.32; p = 0.37), one-year (RR 0.79; 95 % CI 0.48–1.32; p = 0.37) and 5-year follow-up (RR 1.09; 95 % CI 0.81–1.46; p = 0.56) were not significantly different. Conclusions: TAVR in low-risk patients with AS results in reduced 1-year all-cause mortality and rehospitalization rates as compared with SAVR. This benefit is attenuated during protracted follow-up.